The Effect of Poverty on Begging Behavior: A Review of Social Pathology and Islamic Guidance and Counseling Approaches - Siti Cahaya; Heldayanti Heldayanti; Nor Fatmah (YASIN, 2026)
Begging remains a complex social issue that continues to challenge public order, social welfare, and human dignity. This problem is closely associated with poverty, limited access to education, and the influence of individuals’ social environments. This study aims to describe the characteristics of begging behavior, identify its triggering factors, analyze its impacts, and propose intervention strategies through an Islamic Guidance and Counseling approach integrated with behavior modification techniques. A qualitative descriptive-analytical method was employed to examine the internal and external dimensions of begging behavior. The findings indicate that begging arises from the interaction between individual internal conditions and external social influences. Internal factors include irrational thinking, dependency tendencies, and limited understanding of religious values, whereas external factors include structural poverty, limited employment opportunities, and a cultural environment that allows or supports begging practices. The phenomenon negatively affects public order, reduces environmental comfort, and reinforces long-term dependence on assistance from others. The study concludes that comprehensive intervention should involve strengthening religious awareness, correcting erroneous thought patterns, developing positive habits, and reinforcing spiritual values. These findings contribute to the study of social pathology and Islamic counseling by demonstrating that an integrated Islamic Guidance and Counseling and behavior modification approach can help individuals develop independence, work motivation, self-worth, and human dignity, thereby reducing dependence on begging.